2016
DOI: 10.1155/2016/1769250
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesized Silver Nanoparticles Used in Preservative Solutions forChrysanthemumcv. Puma

Abstract: The use of pulse solutions containing antimicrobials has been reported, but more research is necessary. To increase vase life and to study their effect on opening inflorescences, silver nanoparticles were used in vase solutions for cv. PumaChrysanthemumstems. The nanoparticles were synthesized biologically usingChenopodium ambrosioidesL. applied at concentrations of 0.01, 0.05, 0.1, 0.5, 1, and 5 mM and compared with a control. Treatments were replicated five times. The stems were cut to 50 cm and observed unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…SPR band values shifted from 447.5 to 459.0 nm with the addition of extract volume from 1 to 9 mL, indicating the effect of extract concentration in the mean diameter of Ag-NPs. López-Carrillo et al [ 31 ] reported, that in general, particle size can be controlled by changing the volume of the reducing agent.…”
Section: Resultsmentioning
confidence: 99%
“…SPR band values shifted from 447.5 to 459.0 nm with the addition of extract volume from 1 to 9 mL, indicating the effect of extract concentration in the mean diameter of Ag-NPs. López-Carrillo et al [ 31 ] reported, that in general, particle size can be controlled by changing the volume of the reducing agent.…”
Section: Resultsmentioning
confidence: 99%
“…Nanosilver at low concentration may act as an effective preservative which not only prevents microbial growth 24,25 , maintaining xylem integrity but also activates protective enzymological activities 26 . Implementation of NS as preservatives has been reported to extend the shelf life of Dianthus 27 , Chrysanthemum 28 , tulip 29 , Gerbera 30 . However most of the preservative aspects of SN and NS have been reported to extend shelf life of economically important flowering twigs, almost no report was obtained that describes their ability to preserve postharvest leaf samples.…”
mentioning
confidence: 99%
“…It must be remarked that the absorbance of peak from solution at pH 6 was higher than that at pH 4. As peak intensity could be related to Ag-NPs concentration, the increase on peak intensity of solution at pH 6 compared to López-Carrillo et al [31], reported that in general, particle size can be controlled by changing the volume of the reducing agent. Peer-reviewed version available at Nanomaterials 2018, 8, 946; doi:10.3390/nano8110946…”
Section: Effect Of Phmentioning
confidence: 92%